Preferences on Policy Options for Ensuring the Financial Sustainability of Healthcare Services in the Kingdom of Saudi Arabia - Huraysi NA; Kattan WM; Alqurashi MA; Fadel BA; Al-Hanawi MK (Dove Medical Press, 2023)
Najwa Ali Huraysi,1,2 Waleed M Kattan,1 Mohamed A Alqurashi,1 Bodour Ayman Fadel,1 Mohammed Khaled Al-Hanawi1,3 1Department of Health Services and Hospital Administration, Faculty of Economics and Administration, King Abdulaziz University, Jeddah, Saudi Arabia; 2Human Resources Planning Department, King Abdulaziz Hospital, Makkah, Saudi Arabia; 3Health Economics Research Group, King Abdulaziz University, Jeddah, Saudi ArabiaCorrespondence: Mohammed Khaled Al-Hanawi, Tel +966 556522222, Email mkalhanawi@kau.edu.saBackground: Escalating global health expenditures pose a threat to healthcare financing sustainability, requiring the exploration of alternative financing policies and resource allocation strategies to curb their adverse effects. The aim of this study was to gather insight into the preferences of healthcare workers, including physicians, nurses, allied healthcare professionals, and healthcare administrators, as well as academics in the field of healthcare management and health sciences in Saudi universities, regarding policy options that can secure the financial sustainability of healthcare services in Saudi Arabia.Methods: A cross-sectional research design was employed, and data were collected through an online self-administered survey from August 2022 to December 2022 in Saudi Arabia. The survey garnered responses from 513 participants hailing from all 13 administrative regions in Saudi Arabia. Analyses were performed using non-parametric statistical tests, specifically the two-sample Mann-Whitney U-test and Kruskal-Wallis test, to determine the statistical significance of differences in the policy ranking and policy feasibility options.Results: The study findings reveal a consensus among stakeholders on the most and least preferred policies. All stakeholders expressed opposition to financing healthcare by diverting resources from defence, social protection, and education, while they favoured policies that entail imposing penalties on health-related issues such as waste management and pollution. Nevertheless, variations among stakeholders were evident in regard to the rankings for specific policies, particularly between healthcare workers and academics. Moreover, the results highlight that tax-based policies are the most feasible approach to generating healthcare funds, despite ranking lower in terms of preferred policies.Conclusion: This study provides a framework for understanding stakeholder preferences on healthcare financing sustainability by ranking 26 policy options according to stakeholder groups. The appropriate mixture of financing mechanisms should be informed by evidence-based and data-driven approaches that consider relevant stakeholder preferences.Keywords: healthcare financing, healthcare policy, preferences, Saudi Arabia, sustainability